AGAMA DI MATA KAUM MUDA: TINJAUAN SUBJEKTIVISME SØREN A. KIERKEGAARD - Krisna Sukma Yogiswari (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
The specific characteristic of the adolescents is their existential. It means that the adolescent’s involvement in term of thought and their era’s situation are closely related to the development of the adolescence itself in the transition from childhood to adolescence. In this transition process, the adolescents have to be able to put their existence between the social transformation and the demand to be mature which come from their social environment. This perspective makes them to be something that is interested to be discussed. This writing will try to give a kind of description about the involvement of adolescents in reading and interpreting theirreligions in the point of view of Soren Kierkegaard’s subjectivism. The discussion will focus on the diversity elements of the adolescents which are closely related to the subjectivity. This aims to describe the characteristics and intensity of the diversity‘s struggle faced by the adolescents which is more existential